2017
DOI: 10.1149/2.0991707jes
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single Crystal and Polycrystalline LiNi0.5Mn0.3Co0.2O2Positive Electrode Materials for High Voltage Li-Ion Cells

Abstract: Single-crystal LiNi 0.5 Mn 0.3 Co 0.2 O 2 (NMC532) with a grain size of 2-3 μm was compared to conventional polycrystalline uncoated NMC532 and polycrystalline Al 2 O 3 -coated materials in this work. Studies were made to determine how single crystal NMC532 material with large grain size could be synthesized. Ultra high precision coulometry (UHPC), in-situ gas measurements and isothermal microcalorimetry were used to make comparative studies of the three materials in Li-ion pouch cells. All the diagnostic meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
295
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 325 publications
(304 citation statements)
references
References 46 publications
7
295
1
1
Order By: Relevance
“…20 This is certainly an underestimate of the depth from which transition metals might dissolve in the NMC532 particles. If 10% of the transition metals in near-surface layers were to dissolve, then this might impact a depth of 5 nm or so which is consistent with many TEM images of reconstructed surfaces on NMC particles after testing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 This is certainly an underestimate of the depth from which transition metals might dissolve in the NMC532 particles. If 10% of the transition metals in near-surface layers were to dissolve, then this might impact a depth of 5 nm or so which is consistent with many TEM images of reconstructed surfaces on NMC particles after testing.…”
Section: Resultsmentioning
confidence: 99%
“…31 Additionally, Li et al found that NMC532/graphire pouch cells with single crystal positive electrode materials, as used in this study, had longer cycling lifetime and better performance than cells with polycrystalline materials. 32 Figure 12 suggests that further reductions in transition metal dissolution and deposition at the negative electrode may have little impact on lifetime, however, more data points are needed, particularly at larger capacity losses, to make an adequate comparison and prediction. Figure 9b showed that the difference in average charge and discharge voltage ( V) increased with cycle number more rapidly as the upper cutoff potential increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative electrodes had compositions of 95.2% active material, 2% carbon black with the remainder being carboxymethyl cellulose (CMC)/styrene butadiene (SBR) binder. The NMC532 used was called SC532 in an earlier publication by Li et al 22 The positive electrode loading was 21.3 mg/cm 2 and the electrodes were calendared to 3.5 g/cm 3 . The positive electrodes were 94% by weight active material with 4% conducting carbon additives and 2% by weight PVDF binder.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21] Recently, J. Li et al showed that single crystal Li[Ni 0.5 Mn 0.3 Co 0.2 ]O 2 (NMC532) materials in NMC532/artificial graphite cells can have excellent long term lifetime with an electrolyte consisting of 2 wt% prop-1-ene-1,3 sultone (PES) + 1 wt % ethylene sulfate (DTD) + 1 wt% tris (trimethylsilyl) phosphite (TTSPi) in 1 M LiPF 6 in ethylene carbonate: ethyl methyl carbonate (3:7 by weight) (this electrolyte is called PES211 here). 22 During testing to 4.4 V at 40…”
mentioning
confidence: 99%